Small price incentives increase women's access to land titles in Tanzania - Ali, D; Collin, M; Deininger, K; Dercon, S; Sandefur, J; Zeitlin, A (Elsevier, 2016)
We present results from a field experiment using price incentives to address two obstacles to women's access to formal land ownership. First, the price of formal land titles is often prohibitive, restricting access for both men and women. Second, when formal titles are issued, men are recorded as the sole owners of household land in the vast majority of cases. In theory, these problems may be in tension: requirements to grant women equal ownership may reduce the overall household demand for titling. In practice, we find no such trade-off: when residents of low-income, unplanned settlements in Dar es Salaam were offered price discounts for formal land titles, demand rose significantly. Price elasticity of demand was unchanged when price discounts were conditional on registering a woman as (co-)owner of household land. Furthermore, conditional price discounts achieved near gender parity in land ownership.